Building brand credibility: The role of involvement, identification, reputation and attachment. (January 2022) - Molinillo, Sebastian; Japutra, Arnold; Ekinci, Yuksel
Abstract: The aim of this study is to propose a conceptual framework for building destination brand credibility. This research proposes a novel framework to explore the antecedents of destination brand credibility based on four constructs: enduring culture involvement, destination brand identification, destination brand reputation and destination brand attachment. The data used to assess the proposed research model was collected through in-person-administered surveys conducted in Indonesia and Spain. The study shows that destination brand credibility is influenced by enduring cultural involvement, destination brand identification and destination brand reputation. In addition, destination brand attachment partially mediates the relationship between destination credibility and the three antecedents. The findings contribute to the relevant literature by improving the knowledge of the antecedents of destination brand attachment and destination brand credibility.